Association of Perceived Stress with Gender and BMI in students appearing in University Entrance Examination - Qurratulain Saleem, Adil Khan, Taif Hameed, Amna Begum, Tanveer Ahmed Ansari, Saleem Ullah Abro (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Students have been found to report high levels of perceived stress in daily life. However, it exerts many effects on students’ health and outcome or output in examinations results. Aim: To determine the association of perceived stress with gender and body mass index (BMI) in students appearing in the university entrance examination. Methods: It is a cross-sectional study was done to find out the association between variables. The total sample size was 498 (401 Female and 88 male) pre-medical and pre-engineering students with a mean age of samples were 18 (SD=±0.83) years. The purposive sampling technique was used to collect the student’s data from aptitude training centers in Karachi from August to September 2021 by applying Sheldon Cohen’s Perceived Stress Scale (PSS-10). Data was analyzed by using SPSS. Results: There was a moderate stress level of perceived stress in students. The perceived stress was significantly associated with gender (<0.01), while no significant association between stress and BMI (>0.45). Practical Implication: This study would be helpful for the parents and teachers to assess the mental health level (perceived stress) of their new generation, who are striving for a bright future. As to train them for positive coping with this stress and train them for dealing effectively with any worrisome circumstances effectively, as to prevent psychological distress and suicidal ideation in young people of society. Conclusion: In this study moderate stress was observed and perceived stress was significantly associated with gender in our study participants. Keywords: Coping, Perceived stress, perceived stress scale‑10, Students.